Synthesis and electrochemistry of biodegradable ligands - iminodiglutaric acid and iminoglutaricsuccinic acid - and their complexes with selected metal ions (Zn²⁺, Cd²⁺, Cu²⁺) - Yohannes Desta, Yonas (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2004.